2017
DOI: 10.1016/j.dss.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Preventing traffic accidents with in-vehicle decision support systems - The impact of accident hotspot warnings on driver behaviour

Abstract: A B S T R A C TDespite continuous investment in road and vehicle safety, as well as improvements in technology standards, the total amount of road traffic accidents has been increasing over the last decades. Consequently, identifying ways of effectively reducing the frequency and severity of traffic accidents is of utmost importance. In light of the depicted challenge, latest studies provide promising evidence that in-vehicle decision support systems (DSSs) can have significant positive effects on driving beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 51 publications
(101 reference statements)
0
28
0
2
Order By: Relevance
“…In a previous paper, we demonstrated that providing drivers with warnings of upcoming accident hotspots improved their driving behaviour through these hazardous locations over time [7]. Additionally, prior simulation studies have shown that in less critical situations contextual warnings are more suitable and preferred by users than a standard stop sign warning [3].…”
Section: Hypothesis Of the Thesismentioning
confidence: 93%
“…In a previous paper, we demonstrated that providing drivers with warnings of upcoming accident hotspots improved their driving behaviour through these hazardous locations over time [7]. Additionally, prior simulation studies have shown that in less critical situations contextual warnings are more suitable and preferred by users than a standard stop sign warning [3].…”
Section: Hypothesis Of the Thesismentioning
confidence: 93%
“…We use the DBSCAN method to identify accident hotspots, following the DBSCAN application and Swiss coordinate system transformation procedure used on the same dataset in [4]. The DBSCAN algorithm takes two parameters for clustering: the minimum number of points within one cluster and the minimum distance between two points in the same cluster.…”
Section: Methodsmentioning
confidence: 99%
“…This classifies elements into clusters such that each cluster has higher element density than the area around it. DBSCAN can efficiently identify clusters of random shapes and discriminate between cluster members and outliers [5], [4].…”
Section: A Hotspot Identification and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, with the knowledge that a potentially dangerous location is ahead, a semi-autonomous vehicle might drive in a more cautious mode to reduce risk or hand over control to the driver to transfer insurance liability. In addition, recent research studies of in-vehicle warning systems have shown that drivers themselves can be encouraged to adapt their driving behaviour at potentially dangerous locations (Kazazi et al, 2015;Ryder et al, 2017;Tey et al, 2011;Werneke and Vollrath, 2013). Ultimately, insurance companies can collaborate with road authorities to improve the road infrastructure that contribute to dangerous locations, and manufactures to better understand vehicle capabilities and advance safety focused offerings (Sheehan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%